2017
DOI: 10.1016/j.molcel.2017.05.035
|View full text |Cite
|
Sign up to set email alerts
|

A Novel RNA Phosphorylation State Enables 5′ End-Dependent Degradation in Escherichia coli

Abstract: SUMMARY RNA modifications that once escaped detection are now thought to be pivotal for governing RNA lifetimes in both prokaryotes and eukaryotes. For example, converting the 5′-terminal triphosphate of bacterial transcripts to a monophosphate triggers 5′-end-dependent degradation by RNase E. However, the existence of diphosphorylated RNA in bacteria has never been reported, and no biological role for such a modification has ever been proposed. By using a novel assay, we show here for representative Escherich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
131
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(134 citation statements)
references
References 52 publications
3
131
0
Order By: Relevance
“…The next study explained some of these observations. This work confirmed that RppH can function on diphosphorylated RNAs in vitro (Luciano, Vasilyev, Richards, Serganov, & Belasco, ) and demonstrated that RppH activity was more than tenfold greater on diphosphorylated RNAs compared to their triphosphorylated counterparts. These data suggested that the diphosphorylated RNAs are the natural substrates of RppH in E. coli .…”
Section: Phosphorylation States Of the 5′‐end Of Bacterial Rnassupporting
confidence: 79%
See 1 more Smart Citation
“…The next study explained some of these observations. This work confirmed that RppH can function on diphosphorylated RNAs in vitro (Luciano, Vasilyev, Richards, Serganov, & Belasco, ) and demonstrated that RppH activity was more than tenfold greater on diphosphorylated RNAs compared to their triphosphorylated counterparts. These data suggested that the diphosphorylated RNAs are the natural substrates of RppH in E. coli .…”
Section: Phosphorylation States Of the 5′‐end Of Bacterial Rnassupporting
confidence: 79%
“…This new method takes advantage of yeast mRNA guanylyltransferase which uses diphosphorylated RNA as a substrate for capping. A combination of PACO and PABLO (Celesnik, Deana, & Belasco, ) made it possible to precisely determine the phosphorylation state for representative E. coli mRNAs (Luciano et al, ). Surprisingly, the triphosphorylated primary transcripts were found to be much less abundant than their di‐ and monophosphorylated counterparts, while rppH knockout resulted in further increase of fraction of diphosphorylated RNAs.…”
Section: Phosphorylation States Of the 5′‐end Of Bacterial Rnasmentioning
confidence: 99%
“…Bacteria use transcript degradation extensively as a strategy for gene regulation [27][28][29][30][31][32][37][38][39]. Degradation helps to tightly couple transcription and translation, such that protein abundances closely match those of transcripts and bacteria can more quickly respond to changes in their environment.…”
Section: Discussionmentioning
confidence: 99%
“…Pinetree employs a directional model of transcript degradation modeled after observations from E. coli [27][28][29]. In E. coli, degradation occurs either from the 5'-end of a newly-synthesized transcript or from the 5'-end of a transcript recently cleaved by an RNase III ribnuclease [30].…”
Section: Degradation Can Produce Gene Expression Patterns Similar To mentioning
confidence: 99%
“…Thus, RNase E processing is significantly enhanced by the removal of the pyrophosphate from the 5′ terminal triphosphate of many primary transcripts. While conversion of the 5′ triphosphate to a 5′ monophosphate was believed to be catalyzed by the RNA pyrophosphohydrolase (RppH) encoded by rppH (13), a recent report suggests that an unidentified enzyme converts the triphosphate to a diphosphate, which is the substrate of choice for the RppH protein (14). Although RNase E prefers to bind to substrates containing a 5′ monophosphate, a number of experiments have demonstrated that it can also cleave both mRNAs and tRNAs using a direct entry mechanism (1519).…”
Section: General Messenger Rna Decaymentioning
confidence: 99%